Use of convalescent plasma in serious patients by COVID-19: Qualitative case series review (Research, Society and Development, 2021)
The objective of this research was to find and evaluate the efficacy and safety of the use of plasma from recovered patients for the treatment of critically ill patients with COVID-19 (SARS-CoV-2), through a series of cases. The search took place in scientific databases such as Lilacs, MEDLINE, Google Academics, Scielo and Science Direct. After applying the filters for advanced search, and tracking by title, the pre-included abstracts were read, then evaluated in full for data extraction and synthesis of information and results. At the end, three case series observational studies were included. The patients in the study were using medications in a parallel way to the procedure (eg: antibiotics, antiviral drugs and steroids). Patients, in general, had improvements in most clinical symptoms, as well as in the decrease in SARS-CoV-2 viral titers, no adverse event was passive to alert. It is concluded that the evidences found in this work are heterogeneous and with a lot of limitations, about transfused dose, time of treatment and criteria to choose the patients, therefore, due to the presented restrictions, it is necessary to carry out clinical trials with outlined study designs, to certify the safety and effectiveness of the treatment.